Removal of Fluoride from Drinking Water by Sorption Using Diatomite Modified with Aluminum Hydroxide - Tesfaye Akafu; Achalu Chimdi; Kefyalew Gomoro (Journal of Analytical Methods in Chemistry)
Exposure to fluoride beyond the recommended level for longer duration causes both dental and skeletal fluorosis. Thus, the development of cost-effective, locally available, and environmentally benign adsorbents for fluoride removal from contaminated water sources is absolutely required. In the present study, diatomaceous earth (diatomite) locally available in Ethiopia, modified by treating it with an aluminum hydroxide solution, was used as an adsorbent for fluoride removal from aqueous solutions. Adsorption experiments were carried out by using batch contact method. The adsorbent was characterized using FT-IR spectroscopy. Effects of different parameters affecting efficiency of fluoride removal such as adsorbent dose, contact time, initial fluoride concentration, and pH were investigated and optimized. The optimum adsorbent dose, contact time, initial fluoride concentration, and pH values were 25 g/L, 180 min, 10 mg/L, and 6.7, respectively. The performance of the adsorbent was also tested under optimum conditions using groundwater samples taken from Hawassa and Ziway. Langmuir and Freundlich isotherm models were applied to describe the equilibrium data. Compared to Langmuir isotherm (R2 = 0.888), the Freundlich isotherm (R2 = 0.985) model was better fitted to describe the adsorption characteristics of fluoride on Al-diatomite. The Langmuir maximum adsorption capacity was 1.67 mg/g. The pseudosecond-order model was found to be more suitable than the pseudofirst-order to describe the adsorption kinetics. The low correlation coefficient value of R2 = 0.596 for the intraparticle diffusion model indicates that the intraparticle diffusion model does not apply to the present studied adsorption system. The maximum fluoride removal was observed to be 89.4% under the optimum conditions which indicated that aluminum hydroxide-modified diatomite can be used as efficient, cheap, and ecofriendly adsorbents for the removal of fluoride from contaminated water.